A Key to Employee Job Satisfaction and Engagement in Balancing Work and Personal Life - Hossain, Sazib; Sampa, Precious (Universidad Francisco de Paula Santander, 2025)
In this research, the critical link between work life balance and job performance, and between employee engagement and job satisfaction is interrogated with an understanding of how these relationships impact people's well-being at work as well as organizational performance. Employing the SATA tool, survey data were analyzed and the results confirmed that work-life balance has positive correlations with job satisfaction. The results hence emphasize work-related policies, flexible work schedules and individual approaches to work-life conflict. How technology makes this model flexible as well as creates challenges for working people is explained, and there are some options to enhance the work-life balance.